Mechanisms of Crystal Growth: From Spiral Steps to Surface Adhesion - Ben Okri (International Journal of Crystalline Materials, 2025)
Crystal growth is a complex interplay between thermodynamic stability and kinetic processes, influenced heavily by the conditions under which crystallization occurs—particularly the degree of supersaturation. This abstract outline three principal regimes of solution-grown crystal growth: defect-driven, two-dimensional, and adhesive growth. At low supersaturation, growth is facilitated at surface defects, such as screw dislocations, where energy barriers to attachment are minimized. This results in the formation of spiraling steps that propagate outward, producing continuous crystal expansion. As supersaturation increases, the reduced energy threshold enables two-dimensional, or "birth-and-spread," growth even on clean surfaces. This regime favors stepped crystal planes and leads to rapid lateral expansion. At very high supersaturation, the energy barrier is sufficiently low to permit random deposition across the surface, promoting rough, adhesive growth characterized by irregular hillocks and diminished surface uniformity. Observations through atomic-force microscopy provide real-time insights into these growth modes, highlighting the direct correlation between supersaturation and the evolving morphology of crystal surfaces. Additionally, the transition between these regimes is not always abrupt; intermediate states often exhibit hybrid features, such as spiraling layers coexisting with terrace nucleation. The role of temperature, solvent dynamics, and additive molecules further complicate the kinetic pathways, occasionally stabilizing metastable crystal faces or inducing anisotropic growth. Understanding these mechanisms is critical for tailoring crystal size, shape, and purity—essential parameters in fields ranging from pharmaceuticals to semiconductor manufacturing. Control over supersaturation and environmental parameters thus serves as a powerful lever in the rational design of crystallization processes for industrial and scientific applications.
Keywords: Supersaturation crystal growth mechanisms defect growth two-dimensional growth adhesive growth